Safety measures in some large-scale garment factories in Metro Manila - Cordero, Jacqueline Pantig
With the aid of a checklist, a systematic observation was done to determine the different conditions which can cause accidents and injuries in the workplace of the three large-scale garment factories located in Metro Manila. The checklist for safety measures was divided into two parts, the first part consisted of safety measures in different garment operations: cutting sewing, pressing and packing; the second part was the general safety measure which include work premise, work environment, machinery, material handling and management. Results revealed that cuts, lacerations, punctures and abrasions were the frequent injuries reported due to mishandling of tools unguarded machines. Two out of the three companies provide safety measures in the cutting area wherein most of the accidents happen. One company provide safety gloves to the cutters to prevent hand injuries while the other company use an 'anti-tripping device' to prevent accident like tripping from the straight cutter's cord. The work premise covers the exits, passageways, floors, stairs, windows, roadways, dangerous areas and fire protection. The three companies provide atleast two unobstructed exits but only one of them has visible exit signs. Two companies are clean and they also provide handrails for the stairs, bars or grills for window openings, signs for roadways and dangerous areas ans waste containers which are being emptied daily. Under fire protection, the three companies trained their workers in the use of the fire-fighting equipment and posted 'No Smoking' signs within the workplace. Two companies provide fire alarms and signs for the location of the fire-fighting equipment. Only one company conducts fire drills and none of the three companies install fire detectors. The work environment includes lighting, ventilation and airborne dusts. The three companies provide local lighting and use lamps with reflectors. Two companies provide automatic emergency lights. All of them provide ventilators, electric fans and masks but none of them provide local exhaust ventilation. None of the three companies provide safety guard and label to the machine but all of them provide handling equipment and storage racks for their materials. Tow companies have already established safety committees and safety rules as part of their safety programs. The three companies also provide first-aiders and first-aid equipment in their workplace. Aside from the safety measures, the three companies provide training and persuasion to promote industrial safety.